Denouncing Racism through Gothic Literature : Case Study: Jesmyn Ward’s Sing, Unburied, Sing2017 - Bey, Khaled; Selt, Afaf (University of Ammar Theledji -Laghouat, 2022)
In the sphere of literary analysis, numerous scholarly studies engaged in the research regarding the metaphorical expression of psychological and social conflicts in Gothic Literature, signifying fear, horror, and haunted architecture. Southern Gothic's rise in the United States created a perplexing question about how these conflicts were represented within another social unit, such as the margin group. This study exhibits the social conflict encircled by racial strife in the south. It investigates the issues of people of color through Jesmyn Ward's novel sing,unburied,sing. By employing a sociological approach, the present dissertation aims to discuss the depiction of racism through Gothic Literature. Following descriptive and analytical methods, this research is quantitatively based on Jesmyn Ward’s novel Sing, Unburied, Sing aiming to highlight the influence of racial discrimination on the social spectrum in the Southern states, the effect of racial biases on mixed-race communities and the unity of families. The dissertation concludes with the possibility of racial conflict as the representation of horror in Southern Gothic Literature. And the employment of color can be considered a footnote to the issue of race